The study on calculating flow pressure for tight oil well - Zhou Hong; Liu Hailong (Journal of Petroleum Exploration and Production Technology, 2018)
Abstract This paper presents a new method to calculate flow pressure for tight oil well with partial penetration fracture. The solution to the diffusivity equation can be obtained using dimensionless transformation, Laplace transformation, Fourier cosine transformation and other mathematical methods. The calculation results of relative simple system are in good agreement with Kuchuk and Brighan’s analytical solution, suggesting that this method in this paper is accurate. The pressure dynamic flow curve can be divided into four stages: transient flow, first linear flow, first radial flow, and boundary dominated flow. The effect of parameters including fracture orientation, fracture length, the degree of penetration, reservoir boundary anisotropy, reservoir boundary conditions and reservoir width on the pressure and pressure derivative was fully investigated in detail. The fracture length mainly affects the early linear flow, and permeability anisotropy mainly affects the mid-radial flow, and the degree of penetration in the reservoir and fracture orientation mainly affect the late spherical flow, and the boundary conditions and reservoir border width mainly affect the control flow. The method can be used to determine the optimal degree of opening shot, vertical permeability and other useful parameters.